Koloniale Tentoonstelling Semarang as an Industrial Tourism Destination - Hanifati, Khusnul (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 11 No 1 (2024): April 2024, 2024)
The idea behind the world exhibitions event was to promote international trade by exhibiting goods, colonial achievements, and the identities of the colonies. However, Georg Simmel’s notes in “The Berlin Trade Exhibition” showed that the exhibitions developed during the nineteenth century specifically responded to the competitive demands of the industrial mode and money economy. Thus, the purpose of the world exhibition is not merely as an annual fair; rather, it has socioeconomic and cultural aspects represented by the colony on a smaller scale. A similar pattern was also found in the Colonial Exhibition of Semarang. As one of the biggest exhibitions held in Southeast Asia in the early 20th century, the exhibition displayed the Dutch Colonial’s highest achievement in the Dutch East Indies. It represents modern life's industrial and technological advancement and temporarily serves as the center of world civilization. Yet there is a distinct contrast between the natives and European visitors, which causes a contradiction between modernism and traditionalism exhibited in the exhibition. This paper examines Koloniale Tentoonstelling Semarang as the representation of an industrial city and an attraction for a touristic destination. It aims to investigate how world exhibitions served not only as platforms for promoting international trade but also as reflections of the socioeconomic and cultural dynamics of the time.  Keywords: exhibition; colonial; Semarang; Sentiling; Tentoonstelling   Abstrak Gagasan di balik kegiatan world exhibitions adalah untuk mempromosikan perdagangan internasional dengan memamerkan barang, pencapaian kolonial, dan identitas koloni. Namun, catatan Georg Simmel dalam “The Berlin Trade Exhibition” menunjukkan bahwa pameran yang dikembangkan di abad kesembilan belas secara khusus menanggapi tuntutan kompetitif industri dan ekonomi. Oleh karena itu, tujuan pameran dunia bukan hanya sebagai pameran tahunan; namun juga memiliki aspek sosial, ekonomi, dan budaya yang diwakili oleh koloni dalam skala yang lebih kecil. Pola serupa juga ditemukan dalam Pameran Kolonial Semarang. Sebagai salah satu eksibisi terbesar yang diselenggarakan di Asia Tenggara di awal abad ke-20, pameran ini menampilkan pencapaian tertinggi Kolonial Belanda di Hindia Belanda. Hal ini mencerminkan kemajuan industri dan teknologi kehidupan modern yang ditampilkan untuk sementara waktu sebagai pusat peradaban dunia. Namun terdapat kondisi yang mencolok antara penduduk asli dan pengunjung dari Eropa, sehingga menimbulkan kontradiksi antara modernisme dan tradisionalisme yang dipamerkan dalam pameran ini. Tulisan ini akan mengkaji Koloniale Tentoonstelling Semarang sebagai representasi kota industri dan daya tarik destinasi wisata. Tulisan ini bertujuan untuk menyelidiki bagaimana pameran dunia tidak hanya berfungsi sebagai wadah untuk mempromosikan perdagangan internasional tetapi juga sebagai cerminan dinamika sosial ekonomi dan budaya pada saat itu. Kata kunci: pameran; kolonial; Semarang; Sentiling; Tentoonstelling